The Financial Times guide to investing : the definitive companion to investment and the financial markets - Arnold, Glen (Financial times guides., 2020)
Glen Arnold, PhD, runs his own equity portfolio from the heart of rural Leicestershire. He used to teach in the City and was a Professor of Investment but concluded that academic life was not nearly as much fun, nor as intellectually stimulating, as making money in the markets. For decades, his research focus explored the question: ‘What works in investment?’ drawing on the ideas of the great investors, academic discoveries and his own experience, good and bad. As well as being author of the UK’s number 1 investment book, The Financial Times Guide to Investing, he wrote the investing classics, The Great Investors, The Financial Times Guide to Value Investing, Get Started In Shares, and The Deals of Warren Buffett. He has also written several market-leading university textbooks including Corporate Financial Management, as well as the best-selling book on banking, The Financial Times Guide to Banking.